A Reflection on 30 Years of Information Research with Professor Tom Wilson - Fulton, Crystal; Wilson, Thomas (Information Research an international electronic journal, 2025)
Introduction. Professor Tom Wilson created Information Research in 1995 as an open access journal for researchers in the field of information science. The journal is now celebrating its 30th anniversary this year, and the leadership of Tom Wilson, Professor Emeritus of University of Sheffield and University of Borås, the original Editor-in-Chief for the last 30 years. Method. An interview with Professor Tom Wilson explored the development and successes of the journal. Results. The journal remains one of the earliest journals that has continued over the years in information science. The journal started as a research newsletter, before becoming a fully-fledged journal that is currently owned by the University of Borås’ Swedish School for Library and Information Science and hosted by the Swedish National Library’s Publicera publication platform. Conclusion. Information Research continues to offer an important scholarly publication venue for researchers, though the nature of the discipline of information sciences may change significantly over the next 30 years.